2011
DOI: 10.1111/j.1540-6210.2011.02413.x
|View full text |Cite
|
Sign up to set email alerts
|

Covert Pay Discrimination: How Authority Predicts Pay Differences between Women and Men

Abstract: Research repeatedly highlights the gap between male and female earnings across the public and private sectors. Th e authors address an overlooked manifestation of pay discrimination against women in the labor market. Using a survey of 384 public sector chief procurement offi cers, they analyze the indirect eff ects of gender on women's pay through the intervening variable of authority. Gender aff ects the amount of authority that is delegated to an employee, which, in turn, aff ects the variance in pay between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 62 publications
9
83
0
1
Order By: Relevance
“…The gender pay gap has been much discussed in both public and private organizations (Alkadry and Tower , ; Ng et al ; Riccucci ; Sneed ; Stivers ). Dating back to Adams's () seminal work on motivation, organizational behaviorists have consistently found that inequity in wages and compensation among employees has harmful effects for morale and results in a variety of problems related to job satisfaction, turnover, and overall performance (Cho and Sai ; Choi ; Hassan ).…”
mentioning
confidence: 99%
“…The gender pay gap has been much discussed in both public and private organizations (Alkadry and Tower , ; Ng et al ; Riccucci ; Sneed ; Stivers ). Dating back to Adams's () seminal work on motivation, organizational behaviorists have consistently found that inequity in wages and compensation among employees has harmful effects for morale and results in a variety of problems related to job satisfaction, turnover, and overall performance (Cho and Sai ; Choi ; Hassan ).…”
mentioning
confidence: 99%
“…Women may actually be penalized by employers, or at least perceive that they would be penalized, if they were to negotiate (Amanatullah & Morris, ; Bowles et al, ). Others have found that women tend to estimate their own value based on their perception of what other women earn; by lowering their pay expectations, women reduce their entitlement to higher starting salary and ability to later negotiate raises (Alkadry & Tower, ; Barron, ). Female genetic counselors may be unaware of their earning potential, as they compare themselves to other women in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the majority of our respondents reported that they were happy with their current salary and that they feel their salary represents the value of their work, regardless of position or gender, which is in contrast to the 2018 PSS finding that respondents in direct patient care positions were less satisfied with their pay and advancement opportunities than those in non‐direct patient care positions (NSGC, ). However, since males in general perceive their own value to be high (Alkadry & Tower, ; Bowles et al, ; Hogue, DuBois, & Fox‐Cardamone, ), male genetic counselors may actually be asking for larger increases in salary, and may be more likely to actually receive those higher asks. In this cohort, men and women earned the same percentage increase in salary per negotiation, but males started out at a higher salary even when they had not attempted any negotiations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the "egalitarian but traditional" framework in the 90s has maintained this role differentiation and fathers continue to have greater power and prestige in the family unit than do mothers (Carrasco & Rohner, 2013;Cotter, Joan, & Reeve, 2011). Within the larger societal context, men continue to dominate high-level positions in organizations and government and women are systematically assigned to positions of lower authority (Alkadry & Tower, 2011). Therefore, we expected that the relational schema of fathers would be strongly associated to other authority figures in society, such that experiences with one's father will influence the development of AR models and the individual's view of the government.…”
Section: Introductionmentioning
confidence: 93%